2011
DOI: 10.15218/zjms.2011.0008
|View full text |Cite
|
Sign up to set email alerts
|

Infestation rate with polyplax spinulosa (burmeister, 1839) among certain laboratory albino rats (rattus norvegicus) in relation to different washing agents in two Erbil city universities

Abstract: Infestation rate with polyplax spinulosa (burmeister, 1839) among certain laboratory albino rats (rattus norvegicus) in relation to different washing agents in two Erbil city universities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…The rodents were Rattus norvegicus, Rattus rattus alexandrinus, Rattus rattus frugivourus, Acomys cahirinus and Mus musculus.The authors noticed also that rodents in Suez Governorate were the highly ectoparasites infested ones. The result of the occurrence of P. spinulosa in rat colonies in two selected animal houses is in agreement with the study done by Koyee et al (2011), in which, they mentioned that the distribution of lice on the rats was very irregular, even when rats were caught at the same time and on the same premises. According to the study of Abo-Elmaged and Desoky (2013), the relation of inter-specific between the rodent species and their ectoparasites showed that not specific relationship between the rodent species and ectoparasites species, and the population fluctuation of rodent ectoparasites took the same trend of the population fluctuation of the rodent species.…”
Section: Ectoparasitic Organisms On Rattus Rattus and R Norvegicussupporting
confidence: 91%
“…The rodents were Rattus norvegicus, Rattus rattus alexandrinus, Rattus rattus frugivourus, Acomys cahirinus and Mus musculus.The authors noticed also that rodents in Suez Governorate were the highly ectoparasites infested ones. The result of the occurrence of P. spinulosa in rat colonies in two selected animal houses is in agreement with the study done by Koyee et al (2011), in which, they mentioned that the distribution of lice on the rats was very irregular, even when rats were caught at the same time and on the same premises. According to the study of Abo-Elmaged and Desoky (2013), the relation of inter-specific between the rodent species and their ectoparasites showed that not specific relationship between the rodent species and ectoparasites species, and the population fluctuation of rodent ectoparasites took the same trend of the population fluctuation of the rodent species.…”
Section: Ectoparasitic Organisms On Rattus Rattus and R Norvegicussupporting
confidence: 91%
“…In terms of the genus Polyplax, it had a wide host spectrum in Iran (Table 1). For instance, Rattus norvegicus was specialized host for Polyplax spinulosa (spiny rat louse) in Iran similar to other studies (Koyee et al 2011;Sanchez-Montes et al 2013). This louse is cosmopolitan parasitic arthropod collected from Ratt spp.…”
Section: Licesupporting
confidence: 77%